Carbapenem Utilization in Critically Ill Patients - Shahrzad Mahini; Alireza Hayatshahi1; Hassan Torkamandi; Kheirollah Gholami; MohammadReza Javadi (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: Drug Utilization Evaluation (DUE) studies are designed to evaluate and improve the rational use of medications. DUEs have focused on drugs used in high risk patients such as critically ill cases in this study. Carbapenems are beta-lactam type antibiotics with broad-spectrum of activity which cover Gram-positive, Gram-negative and anaerobic bacteria. The heavy use of carbapenems (imipenem or meropenm) could increase the risk of multi-drug resistant (MDR) pathogens. Methods: This study was a prospective and cross sectional study performed at three intensive care units (ICUs) of Shariati hospital, affiliated with Tehran University of Medical Sciences. The study was conducted from April 2012 to May 2013. All of the patients were on imipenem or meropenem as an empiric treatment or based upon microbiology culture results included in the study. Results: Total of 68 patients in three ICU wards evaluated. The most common diagnosis was Central Nervous System (CNS) infections and meningitis (36.8%). The most common microorganism derived from the patient's specimen was Acinetobacter spp. (28%). Overall initial treatment for thirty five patients (51.4%) was justified versus nineteen cases (27.9%) of unjustified. For 14 patients (20.5%) empiric treatment was justified, but continuation of treatment was unjustified. Conclusion: The result of the study showed that empiric therapy was justified in most cases (72%), but according to the culture results, continuation of treatment in several cases was unjustified (47%).